2021
DOI: 10.1007/s10851-021-01054-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Tightness of Semidefinite Relaxations for Rotation Estimation

Abstract: Why is it that semidefinite relaxations have been so successful in numerous applications in computer vision and robotics for solving non-convex optimization problems involving rotations? In studying the empirical performance, we note that there are few failure cases reported in the literature, in particular for estimation problems with a single rotation, motivating us to gain further theoretical understanding. A general framework based on tools from algebraic geometry is introduced for analyzing the power of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…A main open problem is to remove Assumption 1. While our SOS solver always returned the optimal solution in practice as expected by [9], there is synthetic input where it should fail [3]. Since in practice the number of required Newton steps was roughly 15, we believe that the running time of our algorithm can be reduced to only 𝑛 + log(1/𝜀).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A main open problem is to remove Assumption 1. While our SOS solver always returned the optimal solution in practice as expected by [9], there is synthetic input where it should fail [3]. Since in practice the number of required Newton steps was roughly 15, we believe that the running time of our algorithm can be reduced to only 𝑛 + log(1/𝜀).…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, recent studies showed that, in the case of computer vision applications, the SOS relaxation usually yields the optimal solution in practice. See possible explanations in [9] and many references therein. However, SOS method either provides a proof, called certificate, that the returned solution is 𝜀-optimal, or states that it failed.…”
Section: Our Approach -Pnp Via Sdp Dualmentioning
confidence: 99%
“…This immediately raises the following question: Are there PnP instances in which the solution of the fourth-degree problem is different from the correct one (i.e., the global minimum of )? To the best of our knowledge, this question was first answered (in the affirmative) in two recent papers [ 11 , 17 ]. These cases appear to be very rare, as described in [ 17 ].…”
Section: The Lasserre Hierarchymentioning
confidence: 96%
“…Lagrangian duality and SDP relaxations were used to tackle the multiple point cloud registration problem. This problem was investigated further in this model, where it was demonstrated that the SDP relaxation is always tight under low-noise regimes [ 151 ]. A study of global optimality requirements for point set registration (PSR) with incomplete data was presented using this approach.…”
Section: Registrationmentioning
confidence: 99%